Complexation of 2,6-helic[6]arene and its derivatives with 1,1′-dimethyl-4,4′-bipyridinium salts and protonated 4,4'-bipyridinium salts: an acid–base controllable complexation - Li, Jing; Shi, Qiang; Han, Ying; Chen, Chuan-Feng (Beilstein Journal of Organic Chemistry, 2019)
2,6-Helic[6]arene and its derivatives were synthesized, and their complexation with 1,1′-dimethyl-4,4′-bipyridinium and protonated 4,4'-bipyridinium salts were investigated in detail. It was found that the helic[6]arene and its derivatives could all form 1:1 complexes with both 1,1′-dimethyl-4,4'-bipyridinium salts and protonated 4,4'-bipyridinium salts in solution and in the solid state. Especially, the helic[6]arene and its derivatives containing 2-hydroxyethoxy or 2-methoxyethoxy groups exhibited stronger complexation with the guests than the other helic[6]arene derivatives for the additional multiple hydrogen bonding interactions between the hosts and the guests, which were evidenced by 1H NMR titrations, X-ray crystal structures and DFT calculations. Moreover, it was also found that the association constants (Ka) of the complexes could be significantly enhanced with larger counteranions of the guests and in less polar solvents. Furthermore, the switchable complexation between the helic[6]arene and protonated 4,4'-bipyridinium salt could be efficiently controlled by acids and bases.
Keywords: 4,4'-bipyridinium salts; complexation; helic[6]arene; hydrogen bond; macrocycles; macrocyclic arene

Supramolecular Chemistry - Steed, J. W.; Atwood, J. L. (John Wiley & Sons, Ltd., 2009)

(untitled) - Han, Y.; Meng, Z.; Ma, Y.-X.; Chen, C.-F. (Acc. Chem. Res., 2014)

(untitled) - Le Poul, N.; Le Mest, Y.; Jabin, I.; Reinaud, O. (Acc. Chem. Res., 2015)

Calixarenes - Asfari, Z.; Böhmer, V.; Harrowfield, J.; Vicens, J.; Saadioui, M. (Kluwer Academic Publishers, 2001)

(untitled) - Guo, D.-S.; Liu, Y. (Acc. Chem. Res., 2014)

(untitled) - Biros, S. M.; Rebek, J., Jr (Chem. Soc. Rev., 2007)

(untitled) - Hardie, M. J. (Chem. Soc. Rev., 2010)

(untitled) - Yu, J.-T.; Huang, Z.-T.; Zheng, Q.-Y. (Org. Biomol. Chem., 2012)

(untitled) - Ogoshi, T.; Yamagishi, T.-a.; Nakamoto, Y. (Chem. Rev., 2016)

(untitled) - Chen, H.; Fan, J.; Hu, X.; Ma, J.; Wang, S.; Li, J.; Yu, Y.; Jia, X.; Li, C. (Chem. Sci., 2015)

(untitled) - Li, B.; Wang, B.; Huang, X.; Dai, L.; Cui, L.; Li, J.; Jia, X.; Li, C. (Angew. Chem., Int. Ed., 2019)

(untitled) - Chen, C.-F.; Han, Y. (Acc. Chem. Res., 2018)

(untitled) - Yang, K.; Pei, Y.; Wen, J.; Pei, Z. (Chem. Commun., 2016)

(untitled) - Ogoshi, T.; Kayama, H.; Yamafuji, D.; Aoki, T.; Yamagishi, T.-a. (Chem. Sci., 2012)

(untitled) - Strutt, N. L.; Forgan, R. S.; Spruell, J. M.; Botros, Y. Y.; Stoddart, J. F. (J. Am. Chem. Soc., 2011)

(untitled) - Shu, X.; Chen, S.; Li, J.; Chen, Z.; Weng, L.; Jia, X.; Li, C. (Chem. Commun., 2012)

(untitled) - Chi, X.; Xue, M.; Yao, Y.; Huang, F. (Org. Lett., 2013)

(untitled) - Xia, W.; Hu, X.-Y.; Chen, Y.; Lin, C.; Wang, L. (Chem. Commun., 2013)

(untitled) - Jie, K.; Zhou, Y.; Yao, Y.; Huang, F. (Chem. Soc. Rev., 2015)

(untitled) - Dondoni, A.; Marra, A. (Chem. Rev., 2010)

(untitled) - Descalzo, A. B.; Martínez-Máñez, R.; Sancenón, F.; Hoffmann, K.; Rurack, K. (Angew. Chem., Int. Ed., 2006)

(untitled) - Xiao, T.; Zhou, L.; Xu, L.; Zhong, W.; Zhao, W.; Sun, X.-Q.; Elmes, R. B. P. (Chin. Chem. Lett., 2019)

(untitled) - Gattuso, G.; Notti, A.; Pappalardo, A.; Parisi, M. F.; Pisagatti, I.; Pappalardo, S.; Garozzo, D.; Messina, A.; Cohen, Y.; Slovak, S. (J. Org. Chem., 2008)

(untitled) - Talotta, C.; De Simone, N. A.; Gaeta, C.; Neri, P. (Org. Lett., 2015)

(untitled) - Fan, J.; Deng, H.; Li, J.; Jia, X.; Li, C. (Chem. Commun., 2013)

(untitled) - Ogoshi, T.; Kitajima, K.; Aoki, T.; Fujinami, S.; Yamagishi, T.-a.; Nakamoto, Y. (J. Org. Chem., 2010)

(untitled) - Wang, S.; Xu, Z.; Wang, T.; Xiao, T.; Hu, X.-Y.; Shen, Y.-Z.; Wang, L. (Nat. Commun., 2018)

(untitled) - Kobayashi, K.; Yamanaka, M. (Chem. Soc. Rev., 2015)

(untitled) - Si, W.; Chen, L.; Hu, X.-B.; Tang, G.; Chen, Z.; Hou, J.-L.; Li, Z.-T. (Angew. Chem., Int. Ed., 2011)

(untitled) - Zhang, G.-W.; Li, P.-F.; Meng, Z.; Wang, H.-X.; Han, Y.; Chen, C.-F. (Angew. Chem., Int. Ed., 2016)

(untitled) - Zhang, G.-W.; Li, P.-F.; Wang, H.-X.; Han, Y.; Chen, C.-F. (Chem. – Eur. J., 2017)

(untitled) - Wang, J.-Q.; Li, J.; Zhang, G.-W.; Chen, C.-F. (J. Org. Chem., 2018)

(untitled) - Shi, Q.; Chen, C.-F. (Org. Lett., 2017)

(untitled) - Shi, Q.; Han, Y.; Chen, C.-F. (Chem. – Asian J., 2017)

(untitled) - Zhang, G.-W.; Shi, Q.; Chen, C.-F. (Chem. Commun., 2017)

(untitled) - Zhang, G.-W.; Han, Y.; Han, Y.; Wang, Y.; Chen, C.-F. (Chem. Commun., 2017)

(untitled) - Han, Y.; Gu, Y.-K.; Guo, J.-B.; Chen, C.-F. (Eur. J. Org. Chem., 2015)

(untitled) - Nagamura, T.; Sakai, K. (J. Chem. Soc., Faraday Trans. 1, 1988)

(untitled) - Han, Y.; Meng, Z.; Chen, C.-F. (Chem. Commun., 2016)

(untitled) - Thordarson, P. (Chem. Soc. Rev., 2011)

(untitled) - Pappalardo, S.; Villari, V.; Slovak, S.; Cohen, Y.; Gattuso, G.; Notti, A.; Pappalardo, A.; Pisagatti, I.; Parisi, M. F. (Chem. – Eur. J., 2007)

(untitled) - Roelens, S.; Vacca, A.; Venturi, C. (Chem. – Eur. J., 2009)

(untitled) - Huang, F.; Jones, J. W.; Slebodnick, C.; Gibson, H. W. (J. Am. Chem. Soc., 2003)

(untitled) - Li, L.; Clarkson, G. J. (Org. Lett., 2007)

(untitled) - Li, C.; Shu, X.; Li, J.; Fan, J.; Chen, Z.; Weng, L.; Jia, X. (Org. Lett., 2012)